Language Style in Beauty Advertisement Marie Claire Magazine - Hamira Dwi Putra; Arman Arman (ELITE: Journal of English Language and Literature, 2019)
This research aims to describe the language style used in Marie Claire Magazine advertisements. The objectives of this research are: (1) to describe the kinds of language style and how they are used in the advertisements, and also (2) to find out the dominant language style used in Marie Claire Magazine. This research uses a descriptive qualitative method. The data source of this research was beauty advertisements from Marie Claire Magazine that issued in November and December 2017. The data were taken from the text of those printed advertisements. The data were analyzed by using a descriptive qualitative method. It gave a sufficient description of the factual data of the phenomena and provided its logical and rational interpretation based on relevant theories. The research findings showed that there were seven types of language styles that commonly appear in advertisement found in Marie Claire Magazine beauty advertisement based on William Well’s theory: simile, metaphor, personification, alliteration, assonance, ellipsis, and hyperbole. Hyperbole was the most used language style in a beauty advertisement Marie Claire Magazine. The application of hyperbole did not only make advertisements attractive and informative but also made them persuasive. Hyperbole also appears because the language of advertisement might be aiming to persuade the consumers to buy the products.